Cold-stored venous allografts in the treatment of critical limb ischaemia - Matia, I; Janousek, L; Marada, T; Adamec, M (European journal of vascular and endovascular surgery, 2007)
OBJECTIVES: To assess the outcome of cold-stored venous allografts in critically ischemic limbs in patients with no ipsilateral autogenous greater saphenous vein. DESIGN: A non-randomised, retrospective, single-center study. METHODS: From September 2000 to June 2006, 46 cold-stored venous allografts obtained during multiorgan harvest were implanted into 44 critically ischaemic limbs of 43 patients. The indication for reconstructions was rest pain (24%) or tissue lost (76%). Sixty-seven percent of procedures were performed as secondary reconstructions, and 61% of veins were anastomosed to tibial or pedal arteries. Thirty-seven percent of patients received prednisone, and 46% tacrolimus as postoperative immunosuppressive therapy. Mean patient follow-up period was 13.3 months (range 1 week to 60 months). RESULTS: The secondary patency rate for the cohort was 83+/-5.6% at 1 month, 64+/-8.2% at 6 months, 57+/-10.0% at 12 months and 46+/-10.7% at 24 months. Limb salvage rate was 96+/-3.1% at 1 month, 78+/-6.9% at 6 months, 71+/-8.1% at 12 months and 50+/-11.8% at 24 months. CONCLUSION: Cold-stored venous allografts are an alternative conduit for limb salvage procedures when ipsilateral autogenous vein is unavailable.
Keywords: senioři; průchodnost cév; Treatment Outcome; senioři nad 80 let; Retrospective Studies; Blood Vessel Prosthesis Implantation; kryoprezervace; výsledek terapie; Cryopreservation; cévní protézy; Middle Aged; Ischemia; mužské pohlaví; Vascular Patency; Follow-Up Studies; ischemie; Lower Extremity; následné studie; Aged, 80 and over; ženské pohlaví; Anastomosis, Surgical; retrospektivní studie; Humans; anastomóza chirurgická; Transplantation, Homologous; lidé středního věku; Blood Vessel Prosthesis; homologní transplantace; cévy - implantace protéz; dolní končetina; Female; Aged; Limb Salvage; záchrana končetiny; lidé; Male